Dampak Implementasi Coretax Terhadap Kepatuhan Wajib Pajak dan Penerimaan Negara - Anisyah Syahra; Imahda Khoirio Furqon (Universitas Katolik Soegijapranata, Semarang, 2026)
This study examines the impact of the Core Tax Administration System (CoreTax) on taxpayer compliance and state revenue in Indonesia. The uniqueness of this research lies in its focus on the early stage of CoreTax implementation, officially launched on January 1, 2025, as part of Indonesia’s tax administration reform agenda. The objectives are to analyze the extent to which CoreTax enhances taxpayer compliance, strengthens revenue collection, and to identify challenges in its adoption. The research object covers individual and corporate taxpayers registered at selected Tax Offices (KPP Pratama) in Central Java and Jakarta as pilot locations. Using a purposive sampling method, the study selected respondents who had experienced both the previous tax systems and CoreTax. Data were collected through questionnaires and interviews, supported by secondary data from government reports and academic sources. Analytical tools employed include Partial Least Square–Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships among variables. The findings reveal that CoreTax positively influences taxpayer compliance through simplified procedures, transparency, and integrated services, which in turn contribute to increasing state revenue. Nevertheless, technical disruptions, limited digital literacy among SMEs, and data security issues remain significant challenges. The study recommends strengthening IT infrastructure, providing continuous taxpayer education, and enhancing cybersecurity standards to optimize the long-term effectiveness of CoreTax.